Racionais Mc’s e Paulo Freire: um diálogo sobre educação na São Paulo dos anos 90 - Faria, Priscilla Prado de (2017)
This research aimed to clarify how throughout the 1990s the Racionais Mc's group intertwined fun and social responsibility within the formation of Rap's own musical style and especially, how through art they established bonds with education, producing knowledge and propagating it through the places that they used to enter. Using what we dare to call here black performance and dialoguing spontaneously with the thoughts of Paulo Freire, they became a pedagogical tool in some schools in the city of São Paulo in 1992